Xanthohumol, a prenylated chalcone derived from hops, inhibits growth and metastasis of melanoma cells - Seitz, Tatjana; Hackl, Christina; Freese, Kim; Dietrich, Peter; Mahli, Abdo; Thasler, Reinhard Manfred; Thasler, Wolfgang Erwin; Lang, Sven Arke; Boßerhoff, Anja Katrin; Hellerbrand, Claus (Cancers, 2021)
Melanoma is one of the most aggressive and lethal cancers worldwide. Despite recent progress in melanoma therapy, the prognosis for metastasized melanoma continues to be poor. Xan-thohumol (XN), a prenylated chalcone derived from hop cones, is known to possess a broad spectrum of chemopreventive and anticancer activities. However, few studies have analyzed functional XN effects on melanoma cells and there have been no previous in vivo studies of its effects on metastasis. The aim of this study was to investigate the impact of XN on the tumorigenic and liver metastatic activity of melanoma cells. XN exhibited dose-dependent cytotoxic effects on human melanoma cell lines (Mel Ju; Mel Im) in vitro. Functional analysis in the subtoxic dose-range revealed that XN dose-dependently inhibited proliferation, colony formation, and migratory activity of melanoma cells. Subtoxic XN doses also induced markers of endoplasmic reticulum stress but inhibited the phosphorylation of the protumorigenic c-Jun N-terminal kinases (JNK). Furthermore, XN effects on hepatic metastasis were analyzed in a syngeneic murine model (splenic injection of murine B16 melanoma cells in C57/BL6 mice). Here, XN significantly reduced the formation of hepatic metastasis. Metastases formed in the liver of XN-treated mice revealed significantly larger areas of central necrosis and lower Ki67 expression scores compared to that of control mice. In conclusion, XN inhibits tumorigenicity of melanoma cells in vitro and significantly reduced hepatic metastasis of melanoma cells in mice. These data, in conjunction with an excellent safety profile that has been confirmed in previous studies, indicate XN as a promising novel agent for the treatment of hepatic (melanoma) metastasis.
CRIS-Team Scopus Importer:2021-02-05
Keywords: Melanoma; Metastasis; Xanthohumol